О праве эксперта присутствовать при совершении процессуальных действий - Щербаковский, М. Г.; Shcherbakovskyi, M. H.; Щербаковський, М. Г.; Михайло Щербаковський (Теорія та практика судової експертизи і криміналістики : зб. наук. пр. – Харків: Право, 2015. – Вип. 15. – С. 163-171, 2015)
Рассмотрены причины участия эксперта в процессуальных действиях, основными из которых являются недоброкачественность представленных на экспертизу материалов и возможность устранения этого только экспертом. Показано отличие участия эксперта от участия специалиста в процессуальных действиях. Раскрыты задачи, которые решает эксперт в ходе процессуальных действий, и особенности тактики их проведения.

The article discusses the reasons for an expert to participate in legal proceedings. The gnoseological reason for that consists of the bad quality of materials subject to examination that renders the examination either completely impossible or compromises objective, reasoned and reliable assessment of the fndings. The procedural reason consists of a proscription for an expert to collect evidence himself or herself. The author investigates into the ways of how an expert can participate in legal proceedings. If the defense invites an expert to participate in the proceedings, then it is recommended that his or her involvement should be in the presence of attesting witnesses and recorded in the protocol. In the course of the legal proceedings an expert has the following tasks: adding initial data, acquiring new initial data, understanding the situation of the incident, acquiring new objects to be studied, including samples for examination. An expert's participation in legal proceedings differs from the participation of a specialist or an examination on the scene of the incident. The author describes the tasks that an expert solves in the course of legal proceedings, the peculiarities of an investigation experiment practices, the selection of samples for an examination, inspection, interrogation.

Розглянуто причини участі експерта в процесуальних діях, основними з яких є недоброякісність наданих на експертизу матеріалів і можливість усунення цього тільки експертом. Показано відмінність участі експерта від участі спеціаліста в процесуальних діях. Розкрито завдання, які вирішує експерт у ході процесуальних дій, і особливості тактики їх проведення.
On the expert’s right to be present at legal proceedings
Про право експерта бути присутнім при вчиненні процесуальних дій
Keywords: Кримінально-процесуальне право. Criminal and Procedure Law. Уголовное процессуальное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; кримінальне провадження; експерт; процесуальні дії; спеціаліст; матеріали для проведення експертизи; тактика; criminal proceedings; expert; legal proceedings; specialist; materials for forensic examination; tactics; уголовное производство; эксперт; процессуальные действия; специалист; материалы для проведения экспертизы